Necesidades de formación en torno a la competencia digital docente: revisión sistemática - Mgter. Viviana BETANCUR-CHICUÉ,Dra. Ana GARCÍA-VALCÁRCEL MUÑOZ-REPISO (Fonseca, Journal of Communication, 2023)
The study about digital competences in teachers (CDD) has been guided in recent years by references such as the European Framework of Digital Competence of teachers DigCompEdu and the Common Framework of Digital Competence of Teachers published by INTEF in Spain. This article aims to identify the areas of digital competence that the literature refers to as less developed in university teachers, as well as the strategies and training needs in this field